Predicting factors of mortality in patients with shock who live at high altitude - Ruíz-Laos, Santíago (2019)
Objective. To determine the predictive factors of mortality in patients with shock who live at high altitude at more than 3250 m.a.s.l. Methods. A prospective, observational and descriptive study was conducted between December 2015 and March 2016, at two Hospitals in Huancayo, Peru. We included 46 patients diagnosed with distributive, hypovolemic or cardiogenic shock. The data collection instrument was a questionnaire. For the statistical analysis, binary and multiple logistic regression were used. It was considered significant p <0.05. Results. The average age was 67 +/- 18 years (range: 9 to 95); 25 (54.3 %) were male and 21 (47.3 %) female. 32 (69.5 %) patients died. The average age of deaths was 70.3 +/- 9.6 years and survivors 50.4 +/- 4.2years; the most frequent type of shock was distributive and the most common comorbidities were respiratory failure, high blood pressure, and diabetes mellitus. The predictive factors associated with mortality were: female sex (85.7 % vs. 14.3 %; p = 0.02; age> 50 years (74.3 % vs. 25.7 %; p = 0.023); have pathology previous (72.7 % vs. 27.3 %; p = 0.013); Central Venous Oxygen Saturation, SVCO2 less than 70 % (73.1 % vs. 26.9 %; p = 0.023). Submit APACHEII> at 11 points and SOFA> at 3 points, were associated with high mortality. Conclusions. The prediction factors associated with mortality were: female  sex, age> 50 years, having a previous pathology, SVCO2 < 70 %, the APACHE II Score and SOFA, in height shows that at low scores there is high mortality.